Pengaruh Waktu Ekskresi terhadap Residu Kafein pada Urine Responden Pengkonsumsi Teh Celup Hitam menggunakan Pereaksi Parry - Anik Eko Novitasari; Nia Nadia Alfatika (Indonesian Journal of Pharmaceutical Education, 2022)
Addictive substance is NAPZA component. Caffeine is one of addictive substance that has psychoactive properties, induce addicted, and as drug for eleminating drowsiness, mood enhancer, performance, and vigilance. This aim study is identification residual of caffeine in urine and urine effect excretion time after consumed a tea to caffeine visible in urine. Black tea is one of caffeine source. Caffeine reabsorbed in tubules kidney and excretion through urine . This study use 10 urine of human as sample examination. Each of them get instruction to consuming of 250 ml tea and record the time after consuming tea till urination. The urine extracted by eter using separating funnel. The urine extract is identified by Parry Reaction in qualitative method. This study has been shown that all of urine sample have contained caffeine residual after consuming tea with green complex colour marked due to Parry Reaction and it visible from 10 minutes until 3 hours after consuming tea. But, this study need some developments about comparing other reaction to identification caffeine in qualitative method, quantitative method to show level of caffeine in and out from body, and special treatment for subjects.